Emotional labour in non-governmental organisations: narrative analysis and theory expansion. (20th August 2019) - Mastracci, Sharon; Adams, Ian
The purpose of this paper is to explore emotional labour in the context of non-governmental organisations (NGOs) using word data from interviews of five NGO directors on their recruitment criteria when hiring staff. We analyse interview transcripts using semiotic clustering. First-order concepts are organised into second-order themes which are summarised as aggregate dimensions to develop a proposition and expand emotional labour theory. We find evidence of emotional labour in NGOs: modelling behaviour for clients, serving as mentors to new staff members, maintaining boundaries between self and clients, suppressing panic in crisis, cognitive reframing, and compartmentalisation. We provide evidence of emotional labour in NGOs, which contributes to emotional labour theory by focusing solely on this important sector of public service. Little research has been done on emotional labour in such organisations, and consistent with prior findings, we find aspects of emotional labour in NGOs can be rewarding and fulfilling as well.